Smoking and Risk of Urolithiasis: Meta-Analysis of Observational Studies - Yue, Ling; Pai, Qiaofeng; Wu, Xiaolin; Zhang, Jinghua (Frontiers in Public Health, 2022)
Background: Earlier studies have warned about the effects of smoking on urolithiasis. Some studies have deemed that smoking has a promoting effect on urolithiasis, whereas others have considered that no inevitable association exists between the two. Therefore, we conducted a meta-analysis to estimate whether smoking is associated with urolithiasis risk. Methods: To identify publications from related observational studies, we performed a search on PubMed, Web of Science, Embase, and the Cochrane Library databases from inception until October 1, 2021. According to the heterogeneity, random-effect model was used to calculate the odds ratios (ORs) and corresponding 95% confidence intervals (CIs). Results: Five articles were included in the meta-analysis, representing data for 20,402 subjects, of which 1,758 (8.62%) had urolithiasis as defined according to the criteria. Three articles are concerned with analysis between ex-smokers and nonsmokers, in which a significant difference was observed (OR=1.73, 95%CI 1.48–2.01). Our comparison of current smokers with nonsmokers in another meta-analysis of three articles revealed no meaningful difference between them (OR=1.08, 95% CI 0.94–1.23). Finally, we separated experimental subjects into ever-smokers and never-smokers and found some significant difference between the two groups in the analysis of three articles (OR=1.31, 95% CI 1.17–1.47). Sensitivity analysis confirmed the stability of the current results. Conclusion: Combined evidence from observational studies demonstrates some significant relation between smoking and urolithiasis. The trend of elevated urolithiasis risk from smoking was found in current smokers vs nonsmokers and ever-smokers vs never-smokers.